Open Innovation the Impact of Social Capital on Tourism Growth Through the Mediating Role of Open Innovation (Case study: The municipality of Khomam County) - Seyed Hamed Hashemi; Hossein Poorghasem (گردشگری و اوقات فراغت)
Abstract